Kepemimpinan Debora Dalam Kitab Hakim-Hakim - Grecetinovitria Merliana Butar-butar; Berlina Simatupang; Atika Rennawaty Nababan (Lembaga Pengembangan Kinerja Dosen, 2024)
In this article, the role and leadership of women during the Old Testament period is discussed, especially focusing on the figure of Deborah. Although Middle Eastern culture during this period tended to give priority to men, many women played significant roles in history, including Deborah, Esther, and Vashti. As the first female judge in Israel, Deborah had a very important role in leading her nation against the oppression and challenges it faced. Her leadership shows that women are capable of having a strong and effective influence in bringing change to society, and underlines that leadership is not a gender issue, but rather about influence, courage and loyalty to God's will.